A co-sensitized approach to efficiently fill the absorption valley, avoid dye aggregation and reduce the charge recombination. (10th October 2016) - Luo, Junsheng; Wan, Zhongquan; Jia, Chunyang; Wang, Yan; Wu, Xiaochun
Graphical abstract: Highlights: Two simple co-sensitizers were synthesized for N719-based DSSCs. The co-sensitizers could avoid dye aggregation and reduce charge recombination. Both J sc and V oc of the co-sensitized DSSCs were enhanced relative to single N719. Co-sensitization of a DSSC with N719 and LD04 exhibited the highest PCE of 8.955%. Abstract: Compared with the development of novel organic dyes, co-sensitization is a much more convenient way to achieve highly efficient dye-sensitized solar cells (DSSCs). Here, two simple donor-(π conjugated spacer)-acceptor dyes, in which hexyloxy-substituted phenyl as an electron donor, cyanoacrylic acid as the electron acceptor and different spacers thiophene (LD03 ) or furan (LD04 ) as the π-linkers, were designed and synthesized as co-sensitizers forN719 -based DSSCs. The photophysical, electrochemical, photovoltaic performances and electrochemical impedance spectroscopy of these DSSCs were investigated in detail. When compared to the DSSCs fabricated from individualN719, the co-sensitized DSSCs (N719 + LD03 andN719 + LD04 ) showed significantly enhanced power conversion efficiencies (PCEs), short-circuit photocurrent density ( J sc ) and open circuit voltage ( V oc ) simultaneously, which owing to the co-sensitizers could effectively overcome the competitive light absorption by I3 − in the electrolyte, avoid dye aggregation and reduce the charge recombination. Consequently, the co-sensitized DSSC (N719 + LD04 ) gave the highest PCE of 8.955% ( J sc = 17.628 mA cm −2, V oc = 0.758 V and fill factor = 0.670), exhibiting an improvement of 13.412% compared to the device sensitized withN719 alone (PCE = 7.896%) under illumination (AM 1.5G, 100 mW cm −2 ).